Robust Computer Vision-Based Detection of Pinching for One and Two-Handed Gesture Input - Wilson, Andy (UIST '06 Proceedings of the 19th annual ACM symposium on User interface software and technology, 2006)
We present a computer vision technique to detect when the user brings their thumb and forefinger together (a pinch gesture) for close-range and relatively controlled viewing circumstances. The technique avoids complex and fragile hand tracking algorithms by detecting the hole formed when the thumb and forefinger are touching; this hole is found by simple analysis of the connected components of the background segmented against the hand. Our Thumb and ForeFinger Interface (TAFFI) demonstrates the technique for cursor control as well as map navigation using one and twohanded interactions.